The Role of Social Media in Indonesia for Business Transformation Strategy - Eliot Simangunsong; Rudy Handoko (Universitas Prasetiya Mulya, 2020)
The rise of social media in today’s digital era is considered important because it helps people communicate and share information online. It is not surprising that ease of sharing information and communicating through social media has an impact on increasing many online activities, including business activities. This phenomenon is an inspiration that researchers can use to uncover the role of social media in Indonesia for business activities by knowing the factors that can influence a social media follower or fans into actual buyers. By surveying users of social media, 546 responses were collected from social media entrepreneurs and social media buyers. The data analysis showed there is enough evidence that social media is being used for business. The frequency of social media usage has strong links to users to use to buy products or do business in that venue. Young people, such as college students, tend to use social media for business more than those with higher levels of education who may already have permanent jobs. Multiple regression analyses have resulted in a proposed model of social media use for business and offers five major factors that influence satisfaction and performance when doing business on social media.Keywords:Social media, Social commerce, Business performance, Entrepreneurs* School of Business and Economics, Universitas Prasetiya Mulya, Kampus Cilandak, Jakarta, Jl. RA. Kartini (TB Simatupang) Cilandak Barat, Jakarta, 12430, Indonesia https://doi.org/10.21632/irjbs.13.1.99-112